Accelerated Sulphate Attack Study on Cement – Metakaolin – Flyash Concretes - Tiwari, Abhay; Kumar, Awadhesh (International Journal of Advanced Engineering Research and Science, 2022)
Durability is that property of concrete which plays the prime role in governing the lifespan and serviceability of a structure with regard to its intended usage. Environmental conditions of the surroundings are the main criteria which decide the longevity and performance of concrete. For understanding the durability of concrete structures, analysis of the impact of chemical attacks may be crucial. As sulphate attacks are predominant chemical attacks on concrete structures, their study can interpret it when they are subjected to deterioration followed by damage. In this study, the effectiveness of ternary blends of OPC with metokaolin (MK) and flyash (FA) in sulphate resistance of concrete exposed to accelerated effect (i.e. by wetting and drying cycles) in 10% solution of sodium sulphate has been investigated. To assess the level of sulfate attack, the changes in strengths of concrete specimens and their weight change were measured after certain numbers of deterioration cycles. Cubes, prisms and cylinders of concrete were tested for compressive, flexural and splitting tensile strengths respectively whereas the weight changes (in percent) were measured for all the specimens. Combination of OPC with MK and FA has proved its effectiveness in improving the resistance against sulphate attack.